PELAKSANAAN PERKAWINAN POLIGAMI PADA MASYARAKAT BATAK TOBA DI KECAMATAN RONGGUR NIHUTA KABUPATEN SAMOSIR PROVINSI SUMATERA UTARA - Simbolon, Tuppal Parasian; Ismi, Hayatul; Hasanah, Ulfia (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2018)
Polygamy in the Batak Society in the past, before Christianity entered the Batak Land,polygamy or more than one wife were common problems. After Christianity replaced the religion ofthe Ancient Batak community, church rules strictly prohibited polygamy. The Samosir District,Longgur Nihuta sub-district, whose population is dominated by the Toba Batak tribe who areProtestant and Catholic, is still very thick with its customs. As happened in Ronggur NihutaSubdistrict, Salaon Dolok Village where there were several polygamous marriages carried out bythe Toba Batak indigenous people, so the authors were interested in raising the title"Implementation of Polygamy Marriage in Toba Batak Communities in Ronggur Nihuta District,Samosir District, North Sumatra Province"The purpose of this essay is: First to find out the factors that cause polygamous marriage inthe Toba Batak Community in Ronggur Nihuta Subdistrict, Samosir Regency, North SumatraProvince, Secondly, to find out what the results of the Polygamy Marriage Implementation in TobaBatak Community in Ronggur Nihuta District, Samosir North Sumatra Province.The type of research used by the author is a type of sociological research that is researchconducted by identifying the law how effective the law is in the community. The data sources usedin this study are primary data obtained directly from observations in the field and secondary data,namely data that provides an explanation of primary data, such as the draft law on the results ofresearch, works from legal circles relating to research. Analysis of this data is done qualitativelyand deductively drawn conclusions.From the results of the problem research there are two main points which are concluded,First, the factors that cause the implementation of polygamous marriage in the Toba Batakcommunity in Ronggur Nihuta Subdistrict Samosir Regency, namely: do not have offspring, the wifedoes not want to be taken to the yard and sex drive (roha Daging ) or the desire to have manyoffspring who do not fulfill the contents of Article 4 of the Marriage Law. Secondly, due to theimplementation of Polygamy Marriage in the Toba Batak Community in Rongur Nihuta District,Samosir Regency, namely: Unregistered marriage and inheritance rights are not clear partieswhere children from various parties feel inherited.Keywords: Polygamy Marriage - Customary Law - Marriage Law